PENGARUH DEFORESTASI TERHADAP TEMPERATUR, KELEMBABAN, CURAH HUJAN, DAN PENYINARAN MATAHARI: STUDI KASUS DI SUMATERA UTARA - Yuni Yolanda (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
Climate change due to deforestation is a hot global issue today. This study analyzes the effect of deforestation on temperature, humidity, rainfall, and sunshine duration in North Sumatra Province during the period 2013-2022. A quantitative approach was used with deforestation data from the Ministry of Environment and Forestry (KLHK) and climate data from the Meteorology, Climatology and Geophysics Agency (BMKG). Pearson Product Moment correlation analysis was performed using SPSS version 29. The results showed that the average deforestation in North Sumatra reached 9,884.79 hectares per year. The correlation analysis showed a very weak to low negative relationship between deforestation and the four climate parameters analyzed, namely rainfall (r = -0.292), sunshine duration (r = -0.173), air temperature (r = -0.086), and air humidity (r = -0.056). Statistically, no significant relationship (p>0.05) was found between deforestation and climate variables, most likely due to the limited number of annual samples. This study identified that local factors such as the presence of the large Lake Toba and the conversion of deforested land to plantations act as moderators of the microclimate. This explains the impact of deforestation on temperature and humidity in this region is not always significant as theoretically assumed. Correlations between climate variables also show complex interactions, such as a very strong negative relationship between temperature and humidity (r=-0.974; p<0.001). This study provides important insights into the complexity of deforestation and microclimate interactions in a unique tropical region such as North Sumatra.